DEVELOPING A SUSTAINABLE WAQF PRODUCT MODEL: A PRELIMINARY STUDY - Mohaiyadin, Norlaila Mazura Hj.; Mardzuki, Khairunnisa; Mat Nawi, Hafizah; Jusoh, Mohd Abdullah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Muamalat is the pulse of Islamic economic and social engagement in daily living, which includes Waqf. Waqf is recognised as a powerful economic driver, in line with Sustainable Development Goal (SDG) 4: Quality Education. However, in-depth studies into the sustainability of the Waqf product model in higher education institutions remain limited. This preliminary study explores the development of a sustainable Waqf Product model at the National Defence University of Malaysia from a religious institutional logic perspective, namely Shariah Compliance. This study adopts a qualitative approach that supports the interpretivism philosophy, specifically an interpretive case study. It employs a judgmental sampling technique by interviewing key players in university Waqf management at the National Defence University of Malaysia (NDUM), along with supporting documents and field notes. Findings indicate the existence of challenges in implementing Waqf at the university, along with potential solutions. Besides, the potential of asset-based Waqf products at NDUM was observed. Theoretically, the findings present the development of a sustainable waqf product model in religious institutional logic and SDG 4: Quality Education perspectives. Practically, it indicates a need for a policy on income generation for the university.